Penerapan Metode Reverse Engineering di Area Pre-Treatment untuk Merancang Ruang Kerja Pembersihan Galon - Putri, Shafa Jasmina Anggita; Mufidah, Ilma; Martini, Sri (eProceedings of Engineering, 2024)
Drinking water is one of the most essential things that people needed for life. Without mineral water, human body will have dehydration and it can create and effect to disorders and infections to the urinary tract. Improved water supply and sanitation, as well as better water resource management, can boost countries' economic growth and contribute significantly to poverty reduction. In Indonesia, different varieties of drinking water are available for purchase by the public and are a necessity for daily life. For instance, there are bottles with capacities of 250 ml, 600 ml, etc., and a jug with a 19 L or even smaller capacity. However, this is where the issues are identified. There are some jugs that fall under the minor defect and major defect categories and are not classified for reuse. The jug’s minor flaw is that it can still be used after a few polishes using the chosen procedure. For instance, a crack that is smaller than the designated size or a dirty jug. The jug's major flaw, however, prevents it from being used any longer because it goes against the explicitly stated company policies. Keywords: Drinking water, Jug, Cleaning Machine, Product Development, Reverse Engineering